Kontribusi Abû Dâwûd Sulaimân Bin Najâh (413-496 H) dalam Penerbitan Mushaf Al-Qur´An: Studi Analisis Kitab Mukhtaşar at-Tabyîn Lihijâ’i at-Tanzîl - Yuni Fatonah; M. Ziyad Ulhaq (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
The contribution of Abû Dâwûd Sulaimân Bin Najâh (413-496 H) in the rules of Rasm Usmani and the Publication of the Mushaf of the Qur ́an was enormous. Although in writing the rules of Rasm Usmani there are many differences, the contribution of Abû Dâwûd has its own distinctive rules in his school, and that is what is characteristic in his rasm book, namely at-Tanzîl. Then the question becomes what is the contribution of the rasm rule that Abû Dâwûd used in the publication of the mushaf-mushaf of the Qur ́an with various qiraats, which is what makes it a reference to the rules in the book of at-Tanzîl. Therefore, in this study the author will examine the book of at-Tanzîl in more depth, and this research will use a historical approach, then the author will examine further related to the rasm rules used as a reference by Abû Dâwûd in the book of at-Tanzîl and the author will explain the contribution and contribution of Abû Dâwûd in the publication of the current mushaf with the rasm rules he uses. The conclusion of the research that the author conducted is that Imam Abû Dâwûd clings to the mushaf of medina and his scholars, also explains more broadly and at length covering the science of rasm, and explains the rules in detail by discussing them starting from verse by verse in sequence. And the Qur ́an that is widespread throughout the world today is a clear proof of the magnitude of Abû Dâwûd's contribution because many countries use the rasm rules chosen by Abû Dâwûd in the writing of the current mushaf.